Longitudinal Reservoir Evaluation Technique for Tight Oil Reservoirs - Yutian Luo; Zhengming Yang; Zhenxing Tang; Sibin Zhou; Jinwei Wu; Qianhua Xiao (Advances in Materials Science and Engineering)
Reservoir evaluation is a method for classifying reservoirs and the description of heterogeneity quantitatively. In this study, according to the characteristics of longitudinal physical properties of tight oil reservoirs, advanced experimental techniques such as nuclear magnetic resonance, high pressure mercury intrusion, and X-ray diffraction were adopted; the flow capacity, reservoir capacity, ability to build an effective displacement system, and the ability to resist damage in reservoir reconstruction were considered as evaluation indexes; average throat radius, percentage of movable fluid, start-up pressure gradient, and the content of clay minerals were taken as the evaluation parameters. On the above basis, a longitudinal evaluation technique for tight oil reservoirs was established. The reservoir was divided into four categories by using this method. The reservoirs with a depth 2306.54 m–2362.07 m were mainly type I and II reservoirs, and the reservoirs with a depth of 2362.07 m–2391.30 m were mainly reservoirs of type II and III. The most effective development was water injection in the upper section and gas injection in the lower section.